Extracorporeal Life Support in Adult Burn Care: A Systematic Review. Issue 6 (June 2023) - Capoccia, Massimo; Maybauer, Dirk M; Brewer, Joseph M; Maybauer, Marc O
We sought to review the role of extracorporeal membrane oxygenation (ECMO) for the management of burn and smoke inhalation injury in the adult patient population. Therefore, we conducted a systematic search of the literature according to specific combination of key words to ascertain the effectiveness of this support strategy. A total of 26 articles were filtered out of 269 and considered suitable for this study. The PICOS approach and PRISMA flow chart were followed for the purposes of our review. Although there is growing evidence supporting the role of ECMO as an option for burn injury in the adult patient population, this strategy should be considered if a likely successful outcome is expected.